Pengolahan Air Bekas Rendaman Cengkeh Dari Suatu Pabrik Rokok Secara Kimia (Koagulasi- Flokulasi) - Samsudin Affandi (Journal of Industrial Process and Chemical Engineering (JOICHE), 2021)
Clove soaking wastewater that is discharged directly into water bodies without being carried out first results in environmental pollution. Researchers made observations for the characteristics of 2 sampling times, with the COD and BOD concentrations for the first sample, respectively, the COD concentration was 5,703.5 ppm and BOD was 2,270.8 ppm. For the second sample, the concentration of COD is 4,181.4 ppm and BOD is 2,020.7 ppm. Therefore, the researchers tried to treat the water from the cloves soaked by coagulation – flocculation processing. The chemical used in the coagulation stage is alum as a coagulant, while at the flocculation stage, polyelectrolyte is used as a flocculant (auxiliary coagulant). The success indicator in this research is the percentage of COD and BOD removal for treated wastewater. This research was conducted in two stages of processing, the first processing using a dose variation of alum, while the second processing using a dose variation of polyelectrolyte. It was found that alum dose added of 3000 ppm resulted in COD removal percentage of 62.6% and BOD of 72.3%, while in the flocculation process the dose of polyelectrolyte (anionic) added 100 ppm and was able to remove COD and BOD by 60% and 32%.Keywords: Coagulation, Flocculation, Alum, Polyelectrolyte